Kinetics of setting between dissimilar crystalline materials under thermo deformation effect - Abramov V.; Bychkov N.; Gustov D. (E3S Web of Conferences, 2023)
It has been established that the kinetic curves of adhesion (strength increase) are of the sigma type with the displacement period of the second stage relative to the first one. The period of this displacement is determined by starting of a marked metal flow over the micro-protrusion contact sections and its passing on the baton into a harder material under the second kind stresses. Activation of the contact surface of a harder material (corundum) occurs due to a handover of the deformation of the surface layer is plastically deformed micro-protrusions (grains) of the metal due to the effect of the second kind of micro-stresses which were much higher minimum yield strength of a harder material, thereby causing plastic deformation of the latter.